Physiological and pharmacological effects of melatonin on remote ischemic perconditioning after myocardial ischemia-reperfusion injury in rats: Role of Cybb, Fas, Nf?B, Irisin signaling pathway - Gul-Kahraman, Kubra; Yilmaz-Bozoglan, Merve; Sahna, Engin (Wiley, 2019)
It has been found that remote organ/limb temporary ischemia, known as remote ischemic conditioning, can provide protection against the formation of lethal ischemic outcome. Current evidence suggests that aging and age-releated comorbidities impair the cardioprotective effects of conditionings. In conjuction with aging, decrease in melatonin synthesis from pineal gland can have role in the pathogenesis of aging and age-related cardiovascular diseases. In this study, we investigated the effects of remote ischemic perconditioning (RIPerC) and physiological and pharmacological concentrations of melatonin on the infarct size, Fas gene, cytochrome b-245 beta chain (Cybb) gene, nuclear factor-kappa B (Nf kappa B), and irisin using an in vivo model of myocardial ischemia/reperfusion (I/R) injury. Sprague-Dawley rats that were divided into two groups first as non-pinealectomized (Non-Px) and pinealectomized (Px), and then (a) Control; (b) I/R (30-minute ischemia, 120-minute reperfusion caused by left coronary artery ligation); (c) I/R + RIPerC (when myocardial ischemia initiated, three cycles of 5-minute occlusion followed by 5-minute reperfusion); (d) I/R + Mel; (e) Px; (f) Px + I/R; (g) Px + I/R + RIPerC; (h) Px + I/R + RIPerC + Mel groups. The infarct size was determined by TTC staining and analyzed by the ImageJ program. Molecular parameters were evaluated by qRT-PCR and Western blot. Results showed that increased infarct size in Non-Px groups decreased with RIPerC and melatonin. However, increased infarct size in Px groups was decreased minimally with RIPerC and significantly decreased with RIPerC + Melatonin. Fold change in Fas gene was associated with the infarct size. RIPerC and melatonin reduced expressions of Cybb, Nf kappa B, and irisin genes. The physiological release and pharmacological concentration of melatonin may improve protective effect of RIPerC against I/R-induced infarct size by modulating Cybb, Fas, Nf kappa B, Irisin signaling pathways.
Keywords: Cybb; Fas; irisin; ischemia-reperfusion; melatonin; Nf kappa B; remote ischemic perconditioning